Does homeownership reduce crime? A radical housing reform in Britain - Disney, Richard (2020)
“Right to Buy” (RTB), a large-scale natural experiment by which incumbent tenants in public housing could buy properties at heavily-subsidised prices, increased the homeownership rate in Britain by over 10 percentage points between 1980 and the late 1990s. This paper studies its impact on crime, showing that RTB generated significant reductions in property and violent crime that persist up to today. The gentrification of incumbent tenants and their behavioural changes were the main drivers of the crime reduction. This is evidence of a novel means by which gentrification, and housing provision, may have contributed to the sizable crime drops observed in several Western economies in the 1990s and early 2000s